Determinants of Customer Preference to Save in Islamic Bank - Afriani, Tia; Asandimitra, Nadia (al-Uqud : Journal of Islamic Economics, 2020)
The widespread use of sharia products and instruments encourages society to save funds in sharia banks. The main purpose of this research is to test the effect of financial literacy, profit sharing, knowledge of customers, gender, age, education, income to saving decisions. The type of research is quantitative research by using a non-probability sampling method with snowball sampling and purposive sampling technique to get a sample of 230 respondents. The object of this research was sharia bank's customers in Surabaya. The data obtained by spreading the questionnaire online and offline contains 41 items of statement and question. The data analysis technique is multiple linear regression that calculated by software package used for the analysis of statistical data. The result found that financial literacy’s of customer has medium effect about 72.1% to their saving decision. The higher level of customer’s financial literacy increases their ability to manage finance and saving. Meanwhile, profit-sharing has an effect to saving decision, as the higher level of profit sharing will raise society’s interest for saving in sharia bank. Otherwise, customer knowledge and demographic factors (gender, age, education and income) have no effect to their saving decision.